2021
DOI: 10.1038/s41598-021-88472-5
|View full text |Cite
|
Sign up to set email alerts
|

Visual marking in mammals first proved by manipulations of brown bear tree debarking

Abstract: The rather limited human ability to understand animal vision and visual signalling has frequently clouded our expectations concerning the visual abilities of other animals. But there are multiple reasons to suspect that visual signalling is more widely employed by animals than previously thought. Because visibility of visual marks depends on the background in which they are seen, species spending most of their time living in dark conditions (e.g., in forests and/or having crepuscular and nocturnal habits) may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 27 publications
(33 reference statements)
0
12
0
Order By: Relevance
“…Because hibernation is facultative in the Cantabrian Mountains, with multiple individuals not hibernating ( Ruiz-Villar et al 2019 ), we expected some marking behaviors to occur even during the hibernation period. Following the procedure of Penteriani et al (2021) , and to trigger the reaction of bears using preexisting marks on focal rubbing trees monitored by camera traps, we concealed the existing visual marks, one or more portions of the trunk where the bark has been removed ( Fig. 1 ), with strips of bark from the same tree species ( Fig.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Because hibernation is facultative in the Cantabrian Mountains, with multiple individuals not hibernating ( Ruiz-Villar et al 2019 ), we expected some marking behaviors to occur even during the hibernation period. Following the procedure of Penteriani et al (2021) , and to trigger the reaction of bears using preexisting marks on focal rubbing trees monitored by camera traps, we concealed the existing visual marks, one or more portions of the trunk where the bark has been removed ( Fig. 1 ), with strips of bark from the same tree species ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Although research on mammal visual signaling is scarce and its role in communication has often been regarded as secondary, especially in crepuscular and nocturnal species, recent studies have shown that visual signaling could represent a more common and important form of mammal communication than previously thought ( Caro et al 2017 ; Penteriani and Delgado 2017 ; Negro et al 2020 ; Penteriani et al 2020 , 2021 ). For example, long-lasting and permanent physical marks such as scratches and bites left by felines and ursids on diverse types of natural (e.g., tree trunks, rocks) and artificial (e.g., wooden poles) elements of the landscape have the potential to play an important role in animal communication ( Cornhill and Kerley 2020 ; Penteriani et al 2021 ).…”
mentioning
confidence: 99%
See 3 more Smart Citations